Revealed Comparative Advantage in Trade Between the Republic of Macedonia and Cefta 2006 - Emilija Miteva-Kacarski (Economic Review: Journal of Economics and Business, 2018)
The aim of this paper is to identify the sectors in which the Republic of Macedonia has a comparative advantage in export to the other member states of CEFTA 2006 (Central European Free Trade Agreement). The revealed comparative advantage of the Republic of Macedonia (RM) in relation to other CEFTA 2006 member states was calculated for the time period of 2006- 2014 by using the Standard International Trade Classification, Revision 4 (SITC, Revision 4). During the research, the following quantitative methods were used: The Index of Trade Openness (ITO), The Trade Balance Index (TBI), The Export Index of Revealed Comparative Advantage (Balassa's RCA), The Export Index of Revealed Symmetric Comparative Advantage (RSCA) and The Index of Comparative Export Performance (CEP). The research results point to the fact that in the case of the Republic of Macedonia, a high index of trade openness was registered in comparison with other CEFTA 2006 member states. Furthermore, the Trade Balance Index shows that in the course of the analyzed time period, the Republic of Macedonia constantly appeared as a net exporter of products in the category of tobacco and beverages. The RCA and RSCA indices mark down positive values in the category of crude materials inedible (except fuels) and in the category of chemical products whereas the CEP index calculated for the category of tobacco and beverages shows a significant comparative advantage of the Republic of Macedonia over other CEFTA 2006 member states.
Keywords: F1; F14; 330; revealed comparative advantage; the Republic of Macedonia; CEFTA 2006